Kebijakan Legislatif Penanganan Perkara Tindak Pidana Perusakan Hutan yang Melampaui Limitasi Waktu Penyidikan - Eduward Hutapea; Nahdiya Sabrina (MLJ Merdeka Law Journal, 2023)
The background of this study is the inability of investigators to always meet the deadline for examining criminal instances of forest destruction set forth in Article 39 of Law Number 18 of 2013 for the Prevention and Eradication of Forest Destruction. In fact, it is still discovered that investigators cannot finish the investigation until the time limit expires, the investigation is not continued by the Public Prosecutor, and there is a condition that the Public Prosecutor cannot finish the continuation of the investigation, which is crucial to investigate. In order to determine how the legislative policy of investigating cases of forest destruction exceeds the time limit and how to regulate the investigation of cases of forest destruction in the future based on the materials existing law, this research is normative in nature. It is conducted in literature using normative qualitative analysis methods and descriptive content analysis methods.  The study's findings demonstrate that the time limit cannot be applied to all criminal investigations involving forest destruction due to a variety of factors. This, along with the fact that there is a P3H Institution that should have a uniform set of standards and the lack of technical provisions for investigators and public prosecutors, calls for a change in policy. Due to this, the study suggests that the time limit not be formulated in law but rather be regulated in technical provisions, completing technical provisions for investigations and complementing provisions for strengthening investigators due to the failure to realize the establishment of a P3H Institution.